Reopenable clip-over-the-line method for closing large mucosal defects following colorectal endoscopic submucosal dissection: A feasibility study - Nomura, Tatsuma; Sugimoto, Shinya; Temma, Taishi; Oyamada, Jun; Ito, Keiichi; Kamei, Akira (Endoscopy International Open, 2023)
Background and study aims Complete closure of large defects after colorectal endoscopic submucosal dissection (ESD) can be problematic, especially in challenging areas or lesions larger than half the lumen circumference. We report a reopenable clip-over-the-line method for such defects and aim to investigate its feasibility through a case series.Patients and methods We retrospectively evaluated data from 30 consecutive patients who underwent ESD with defect closure using the reopenable clip-over-the-line method between October 2020 and September 2022. This method requires the first clip-with-line grasp of the oral side's defect edge and muscle layer. The next reopenable clip (with a line fed through a hole in the reopenable clip tooth) is placed on the opposing mucosal defect edge and muscle layer. This process is repeated until complete closure. The primary study outcome was the rate of complete mucosal defect closure. We also reported post-procedure bleeding or perforation.Results The median dimensions of the resected specimens were 45 mm (range, 35–70) by 39 mm (range, 29–60). Complete closure was achieved for all defects, including nine rectal defects, of which three bordered the anal verge. Of the 30 defects included in this study, nine were larger than half the lumen circumference. The median closure time was 25 minutes (range, 14–52), and the median clip number was 17 (range, 9–42). No post-procedure bleeding or perforation occurred.Conclusions The reopenable clip-over-the-line method is a feasible technique for the complete closure of large colorectal defects after endoscopic submucosal dissection, regardless of location.